ANALISIS PENERAPAN MANAJEMAN PENGELOAAN KEUANGAN HASIL TANGKAP IKAN PADA NELAYAN KAPAL MOTOR PUKAT CINCIN (PURSE CEINE) DESA BANDARAN KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Suhaimi; Mohamad Suhud; Abdul Hamid; Siti Romlah (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2023)
Bandaran Village is a village on the south coast of Madura Island where almost 75% of the population work as fishermen. There are more than 150 fishermen using purse seines with a total workforce of 35 people per boat. With the number of crew members, there is a division of labor and management of financial management of the fish catch obtained by each ship. The form of this research is descriptive qualitative where the data describes the phenomena and analysis that occurred during this research in the field. and the sample is people who work as fishermen in the airport village. The techniques used are interviews, observation, documentation, data presentation, verification. The management of the division of labor managed by the captain of the ship is good where in managing the ship the captain is able to plan, organize, place, direct and supervise his crew to continue working according to their respective procedures and duties. The financial management that is applied does not meet the correct financial management standards, but with the application that is already running it is good enough for a class of fishing boats whose education is only at elementary school.